2019
DOI: 10.7717/peerj.7142
|View full text |Cite
|
Sign up to set email alerts
|

Optical microscopic study of surface morphology and filtering efficiency of face masks

Abstract: BackgroundLow-cost face masks made from different cloth materials are very common in developing countries. The cloth masks (CM) are usually double layered with stretchable ear loops. It is common practice to use such masks for months after multiple washing and drying cycles. If a CM is used for long time, the ear loops become stretched. The loop needs to be knotted to make the mask loop fit better on the face. It is not clear how washing and drying and stretching practices change the quality of a CM. The parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(131 citation statements)
references
References 27 publications
6
114
0
4
Order By: Relevance
“…One study on one fabric face mask showed a decrease in filtration efficiency with washing. 11 All fabric materials were tested after one wash and dry in a home machine.…”
mentioning
confidence: 99%
“…One study on one fabric face mask showed a decrease in filtration efficiency with washing. 11 All fabric materials were tested after one wash and dry in a home machine.…”
mentioning
confidence: 99%
“…In such emergency situations, locally made cloth mask are widely used due to low cost and added advantage of decontamination and washing between uses [31] . The particulate matter filtering performance of cloth mask have been found lower than commercially available surgical masks and respirators [52][53][54] . Davies et al [71] reported the filtering efficiency of two layered cloth mask made from commonly available fabrics using bacteriophase A cluster randomized trial of cloth masks in healthcare workers in hospital settings reported that influenza like illness was higher in health care workers who wore cloth mask than those who wore surgical mask [28] .…”
Section: Measurement Of Filtering Efficiencymentioning
confidence: 89%
“…Also, in cloth face mask the pores are much bigger (figures 2c and d). This arrangement does not provide gradient filtering and explains why cloth face masks have filtering efficiency than surgical face mask [52][53][54] . [52] .…”
Section: Filter Media Used In Face Mask and Respiratormentioning
confidence: 99%
“…The effectiveness of a mask depends on the type of material (14) , the particle size and aerosol charge (15) and can be measured according to its filtering efficiency. A mask is considered effective if its filtering capacity is greater than 95%.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of cotton masks, WHO recommends washing them with household detergent (24) . Furthermore, use of masks by the population conveys a false sense of security, inducing the individual to devalue the set of preventive measures against the pandemic by COVID-19 (14)(15)22) .…”
Section: General Population VImentioning
confidence: 99%